ANALISIS PEMBIAYAAN SYARIAH ATAS NILAI TAMBAH PRODUK PERTANIAN - Abdul Holik; Aisyah Rosadi (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2013)
This research aims to find the impact of sharia finance toward the value-added of agricultural products in Indonesia, by using the data from 2005 until 2011. The OLS method was used to findcausal relationship among the variables, i.e. the value-added of agricultural products, manufacture products, and sharia finance. The result showed that sharia finance had positive significant impact on the value-added of agricultural products; meanwhile value-added of manufacture product had negative significant impact on the value-added of agricultural products. This is an evidence the important role of sharia finance in boosting agricultural value-added in the long-run, as well as for other industries.